Strategi Pengembangan Agribisnis Kopi Arabika di Kabupaten Simalungun - Siadari, Ulidesi; Jamhari, Jamhari; Masyhuri, Masyhuri (Sekolah Pascasarjana UGM, 2020)
Coffee is an important export commodity for Indonesia, which contributes a sizeable foreign exchange. Indonesian coffee production is still fluctuating. Simalungun is a regency in North Sumatera province which have significant potential for the development of Arabica coffee commodity. However, there are some obstacles in the development of arabica coffee farming including land resources utilization, aspects of cultivation, harvest and post-harvest, and institutional aspects. Therefore, it is necessary to formulate business development strategies for arabica coffe agribusiness. This study aims to determine priority strategies from various alternatives in developing Arabica coffee. Determination of the location of the study was done purposively. Respondents in this study were experts or key people who understoodarabika coffee agribusiness. The method used in determining respondents is purposive sampling. Primary data is obtained through direct interviews conducted with respondents and secondary data obtained from books, journals and books of the agricultural service report. Several alternatives in this study were determined based on the results of discussions with the experts and also based on the literature and previous research. Some of these alternatives are then compared in a questionnaire for the respondents. The comparison is then processed using the analytic hierarchy process method (AHP). Data processing is done using the expert choice application so that a priority alternative appears. The study oncludes that based on analytic hierarchy process, the priority strategy is developing the capacity of human resources (HR) of agribusiness actors